PENGARUH MORDANTING DAN PEMANASAN PADA PEWARNAAN KAIN DARI PEWARNA ALAMI ANTOSIANIN EKSTRAK MASERASI BUNGA ROSELLA (Hibiscus sabdariffa L.) - NURCAHYO, HERU (Universitas Bhakti Kencana, 2019)
The choice of roselle in this study was due to the anthocyanin content in the crown of roselle (Hibiscus sabdariffa L) 0.795% and gave a strong color pigmentation such as red, orange, purple, and blue. The purpose of this research is the application of natural dyes as natural dyes that are economical and friendly to the environment. This research is an experimental research laboratory (experimental research) using a Completely Randomized Design (RAL) with three different formatting factors in mordanting treatment and differences in the immersion time of 10 minutes, 30 minutes and 60 minutes by heating the oven to a temperature of 500C and fixation using alum of 10% w / v. testing includes color homogeneity test, organoleptic test covering color and smoothness level with the hedonic scale method, color value test, and colorfastness using Straining Scale method. the best treatment seen by the hedonic scaled analysis method using one-sample t-Test showed that different concentration treatments affect the color and smoothness by using mordan alum. The dyeing time affects the color density based on the test of the intensity of the color